Strategies and guidelines for urban sustainability: the explosion of micromobility from Covid-19 - Gaglione, Federica (TeMA - Journal of Land Use, Mobility and Environment, 2020)
Starting from the relationship between urban planning and mobility management, TeMA has gradually expanded the view of the covered topics, always following a rigorous scientific in-depth analysis. This section of the Journal, Review Notes, is the expression of a continuous updating of emerging topics concerning relationships among urban planning, mobility and environment, through a collection of short scientific papers written by young researchers. The Review Notes are made of five parts. Each section examines a specific aspect of the broader information storage within the main interests of TeMA Journal. In particular: the Town Planning International Rules and Legislation Overview section aims at presenting the latest updates in the territorial and urban legislative sphere. Urban patterns and their intrinsic relationships have completely changed since Covid-19. In particular, the mobility subsystem has undergone a significant change, inducing users to use "soft" such as micromobility. Micromobility is now on the rise, especially in large cities, but at the same time the lack of dedicated routes pushes researchers and technicians in the area to find solutions capable of providing rules to users. This section examines the legislative decrees issued by the Italian government to promote a sustainable mode of travel for cities such as micromobility.